Kutau Martial Ritual Of Community In The Suro Village - Lidiantari, Aulini; Muliati, Roza; Nursyirwan; Minawati, Rosta (Indonesian Scientific Publication, 2023)
This paper discusses the kutau martial ritual in the people of Suro Village, Muara Beliti District, Musi Rawas Regency. Kutau is one of the ancestral heritage where there are rituals in practice that are carried out. Kutau is in the form of a traditional martial art that developed within the people of Suro Village. Using a qualitative approach, the purpose of this study was to find out the forms of rituals in kutau self-defense and the functions of the kutau rituals in the Suro community. Research data was collected from observation, interviews, and documentation. The data obtained was then analyzed using a ritual approach by Victor Turner and function by Talcot Parsons. The results of the study show that the kutau martial arts ritual is a communication medium for the kutau group and the ancestors who inherited the kutau knowledge, which is related to the beliefs of the Suro people. The sustainability of kutau is due to the achievement of the latency function of the kutau group, so that the system built is able to survive and adapt in society.